Desorption induced GaN quantum dots on (0001) AlN by MOVPE. Issue 9 (21st August 2015) - Bellmann, Konrad; Tabataba‐Vakili, Farsane; Wernicke, Tim; Strittmatter, Andre; Callsen, Gordon; Hoffmann, Axel; Kneissl, Michael
<x xml:space="preserve">Abstract</x> GaN quantum dots (QDs) are realized on (0001) AlN templates by growing a thin GaN layer on an AlN buffer layer and applying a subsequent desorption step without ammonia present. A growth interruption (GRI), which is commonly applied after the GaN growth allowing for QD formation, is systematically investigated regarding the temperature, duration and initial GaN coverage. Without GRI the initial GaN layer exhibits a two‐dimensional nonuniform growth at the step edges. In this study, the surface morphology only changes significantly if the GRI is performed without ammonia exposure. Thus, an initial two‐dimensional GaN layer can be shaped into three‐dimensional nanostructures. Presented coverage studies by atomic force microscopy (AFM) show desorption as the main driving force for island evolution. By tailoring the growth parameters, GaN QDs can be achieved. Uncapped GaN samples exhibit QDs with 1.2 nm in height and 30 nm in diameter. Additionally, capped GaN QDs exhibit excitonic luminescence lines at about 4.3 eV with FWHM down to 2 meV and an excitonic fine structure splitting of 7 meV. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)